Application of Whole Exome Sequencing in Congenital Secretory Diarrhea Diagnosis. Issue 6 (June 2019) - Gupta, Ashish; Sanville, Julie; Menz, Timothy; Warner, Neil; Muise, Aleixo M.; Fiedler, Karoline; Martín, Martín G.; Padbury, James; Phornphutkul, Chanika; Sanchez-Esteban, Juan; Cerezo, Carolina S.
Abstract : Supplemental Digital Content is available in the text